2003
DOI: 10.1097/01.phm.0000098504.78524.e2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Holistic Wellness Program for Persons with Spinal Cord Injury

Abstract: Within-group comparisons suggest improvements in several areas of the participants' overall health behaviors. These findings, although preliminary, emphasize the potential role of health behaviors in positively influencing long-term health outcomes and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 11 publications
2
54
0
5
Order By: Relevance
“…However, in the latter study, the enhanced HSE levels of persons in the intervention group did not differ from the HSE levels of the control group. 60 PC was not improved in the identified intervention studies. 43,47,55 Overall, sample sizes for SE-intervention studies were small (27ono44), but larger for PC-intervention studies (37ono234).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…However, in the latter study, the enhanced HSE levels of persons in the intervention group did not differ from the HSE levels of the control group. 60 PC was not improved in the identified intervention studies. 43,47,55 Overall, sample sizes for SE-intervention studies were small (27ono44), but larger for PC-intervention studies (37ono234).…”
Section: Resultsmentioning
confidence: 80%
“…Five randomized controlled trials were identified and rated with PEDro. 35,47,56,58,60 On average, studies achieved a score of 7.4 out of 11. Therapists and assessors were not blinded and only two studies 56,58 performed concealed allocation and 'intention to treat' analyses.…”
Section: Study Qualitymentioning
confidence: 99%
“…13 Other variables like age, neurological level of injury, functional recovery of mobility, social support and self-care also have an important role. 14,15 In our study, age was identified to be negatively associated with knowledge and knowledge acquisition as well. Furlan and Fehlings 16 identified that older SCI subjects had worse functional recovery compared with younger patients.…”
Section: Discussionmentioning
confidence: 86%
“…The differences in the number of patients with poor (0-8), average (9)(10)(11)(12), and good knowledge (13)(14)(15)(16)(17)(18)(19)(20) between the different age classifications (age at injury) were calculated using a w 2 or Fisher's exact test as appropriate.…”
Section: Statisticsmentioning
confidence: 99%
“…Therefore, encouraging an active lifestyle is important in this population. Interventions conducted to promote PA in persons with SCI showed moderate benefits [19,20]. Furthermore, none of these interventions were • Persons with long-term SCI benefit from a higher activity level in terms of health-and psychological benefits.…”
Section: Introductionmentioning
confidence: 99%